Utilization Of Rfid In Building An Order Of Administration And Distribution In Material Warehouse Installation Gatot Soebroto Hospital Indonesia - Ramlan, Ramlan (International Journal of Business, Law, and Education, 2023)
RSPAD Gatot Soebroto is a type A government hospital with the highest referral in the ranks of the TNI and serves as a health service for the general public and continues to strive to improve the quality of excellent health services for each patient. For this reason, the Gatot Soebroto Army Hospital always provides medical supplies generally stored in the material warehouse installation. The Gatot Soebroto Army Hospital's material warehouse installation consists of a general and Health material warehouse. For health services to run well, improving the quality of the material warehouse installation unit is necessary. The development of Radio Frequency Identification (RFID) technology is increasing rapidly from year to year; its benefits can be integrated into managing material warehouse installations to build orderly administration and distribution of material medical supplies needed in each installation unit at the Gatot Soebroto Army Hospital. Through the warehousing application with the RFID application, it is hoped that the process of procurement, receipt, storage, and distribution of material for medical supplies will be more easily controlled, both for evaluation of use, as well as evaluation of stock-taking of supplies which will later become the basis for material procurement for the following year. In addition, RFID also controls the material distribution designation and year of procurement. So that the distribution of material as hospital assets will be recorded accurately and the health services provided can also run well and have good quality.